Health Literacy on Sodium Restriction and Associated Factors among Patients with Hypertension in Phnom Penh, Cambodia - Suon, Monirath; Ruaisungnoen, Wasana (Nursing Science Journal of Thailand, 2019)
Purpose: To determine the level of health literacy on sodium restriction and factors associated with health literacy on sodium restriction among patients with hypertension in Phnom Penh, Cambodia. Designs: A cross-sectional descriptive design was conducted among 317 outpatients with hypertension at the Khmer-Soviet Friendship hospital. Data were collected with the self-report questionnaire comprising demographic characteristics, literacy skills, knowledge about hypertension and sodium restriction, health literacy on sodium restriction, and health professional communication. Descriptive statistic and linear regression were performed. Main findings: The average health literacy on sodium restriction among patients with hypertension in this study was35.38 (SD = 9.60). Four factors including educational level (β = .159, p = .003), literacy skills (β = .125, p = .019), knowledge about hypertension and sodium restriction (β = .266, p < .001), and health professional communication (β = .359, p < .001) were significantly associated with the level of health literacy on sodium restriction. Conclusion and recommendations: Patients with hypertension in Phnom Penh, Cambodia had limited health literacy on sodium restriction. Education level, literacy skills, knowledge about hypertension and sodium restriction, and health professional communication were positively associated with health literacy on sodium restriction.Consequently,healthcare provider should promote health literacy on sodium restriction by improving patients’ literacy skills and knowledge about hypertension and sodium restriction through supportive communication especially among patients with low education level.